2015
DOI: 10.1007/s11832-015-0663-y
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of foot abduction brace reduces the rate of surgery in Ponseti-treated idiopathic club feet

Abstract: Purpose There is conflicting evidence related to factors affecting the rates of recurrence of idiopathic club feet using the Ponseti method. We attempt to evaluate the predictors of success and failure in our physiotherapy-led Ponseti club foot clinic. Methods We evaluated 189 children with 279 club feet with a mean follow-up of 6.3 years for the following: Pirani score at presentation, number of casts for correction, indication for Achilles tenotomy, and the duration of foot abduction brace (FAB) use, in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Better brace use has been repeatedly found to reduce relapse [18, 2325] and has been reported in a 6-years follow up study of 189 cases (279 ft) [26]. This study found that surgery was more likely if brace use stopped before 28 months of use, versus cases wearing the brace for 33 months or more were less likely to have required surgery [26]. Brace use to ‘school age’ (approximating ages 5 to 6 years) is usually advised as part of the Ponseti maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…Better brace use has been repeatedly found to reduce relapse [18, 2325] and has been reported in a 6-years follow up study of 189 cases (279 ft) [26]. This study found that surgery was more likely if brace use stopped before 28 months of use, versus cases wearing the brace for 33 months or more were less likely to have required surgery [26]. Brace use to ‘school age’ (approximating ages 5 to 6 years) is usually advised as part of the Ponseti maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…When introducing the Ponseti method, the bracing protocol was changed, and it was recommended to use the brace for 4 years. The importance of brace compliance in Ponseti treatment is described in a recent study [ 30 ] and a systematic review [ 31 ]. Brace compliance was good in the Ponseti group in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors find a relation between recurrences and brace compliance. 16 , 18 , 25 Even if Ponseti recommended using the brace for four years, the definition of compliance/ non-compliance varies greatly. Some report non-compliance as complete discontinuation of the use of the brace, 25 , 26 while others have defined good compliance as night time bracing until 12 months of age, and poor compliance as termination before that.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Poor compliance with the brace is a common problem in the treatment of clubfeet 4 , 16 , 17 and prolonged use of the brace improves the results. 18 Both brace compliance and type of brace might explain the increased rate of surgery over time in our patient cohort, and the aim of the present study was to search for potential differences between children treated with a bilateral foot abduction brace and children treated with a unilateral brace at follow-up of 8 to 11 years of age.…”
Section: Introductionmentioning
confidence: 97%